1995
DOI: 10.1007/bf00633709
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effects of deltamethrin on some biochemical parameters of carp (Cyprinus carpio L.)

Abstract: Thein vivo effects of deltamethrin (DM) on the blood sugar level, the acetylcholinesterase (AChE, EC 3.1.1.7) activities of the blood serum and various organs (heart, liver and intestine), the lactate dehydrogenase (LDH, EC 1.1.2.3), glutamic-oxaloacetic transaminase (GOT, EC 2.6.1.1), and glutamic-pyruvic transaminase (GPT, EC 2.6.1.2) activities of the blood serum, the adenosine triphosphatases (EC 3.6.1.3; Na(+)/K(+)-ATPase and Mg(2+)-ATPase) activities of the erythrocyte plasma membrane and the catalase (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…A similar reduction in CarE activity in spiders after dimethoate exposure has been reported previously (Babczynska et al, 2006). The significant, reduction in AChE activity after fenvalerate exposure is consistent with reductions observed in other invertebrate and vertebrate groups exposed to pyrethroids (Szegletes et al, 1995;Ibrahim et al, 1998), although increased AChE activity has also been observed (Badiou et al, 2008). The accompanying reduction in CarE activity after fenvalerate exposure is unexpected given that hydrolysis of pyrethroids by carboxylesterases is a rapid reaction in which the enzyme is returned (not destroyed) and therefore activity should be maintained.…”
Section: Discussionsupporting
confidence: 88%
“…A similar reduction in CarE activity in spiders after dimethoate exposure has been reported previously (Babczynska et al, 2006). The significant, reduction in AChE activity after fenvalerate exposure is consistent with reductions observed in other invertebrate and vertebrate groups exposed to pyrethroids (Szegletes et al, 1995;Ibrahim et al, 1998), although increased AChE activity has also been observed (Badiou et al, 2008). The accompanying reduction in CarE activity after fenvalerate exposure is unexpected given that hydrolysis of pyrethroids by carboxylesterases is a rapid reaction in which the enzyme is returned (not destroyed) and therefore activity should be maintained.…”
Section: Discussionsupporting
confidence: 88%
“…Similar lesions were observed only in rats treated with deltamethrin at doses of 25 mg kg −1 (Luty‐Tos et al., 2001), which were also high. The drug can cause changes in the erythrocyte profile and plasma total protein of carp (Szegletes et al., 1995; Svobodova et al., 2003) and is known to induce blockage of the expression of choline acetyltransferase in the bulbus axon terminals synapsing with the lateral dendrites of the Mauther cells and at high doses can induce neuropathy in fish (Csillik et al., 2000). At doses of 0.01–0.05 mg L −1 , however, this drug has been proved safe to use and an exceptional license for the drug has been granted in the past in Greece in order to treat sea lice.…”
Section: Discussionmentioning
confidence: 99%
“…These pesticides include organophosphates, carbamates, and some organochlorines [5,18,31,32]. In addition, there are reports indicating pyrethroids' effect on the cholinergic system [1,13,30], although pyrethroids appear to have multiple mechanisms of action [4,11,26,33,34,36]. The immediate result of AChE inhibition is an increase in acetylcholine that may alter one or more steps in subsequent cholinergic pathways.…”
Section: Introductionmentioning
confidence: 99%